An estimate assay for low-level exposure to ionizing radiation based on mass spectrometry quantification of γ-H2AX in human peripheral blood lymphocytes - Zhao, Hongling; Qu, Minmin; Li, Yuchen; Wen, Ke; Xu, Hua; Song, Man; Xie, Dafei; Ao, Xingkun; Gong, Yihao; Sui, Li; Guan, Hua; Zhou, Pingkun; et al. (Frontiers in Public Health, 2022)
Exposure to environmental ionizing radiation (IR) is ubiquitous, and large-dose exposure to IR is known to cause DNA damage and genotoxicity which is associated with an increased risk of cancer. Whether such detrimental effects are caused by exposure to low-dose IR is still debated. Therefore, rapid and early estimation of absorbed doses of IR in individuals, especially at low levels, using radiation response markers is a pivotal step for early triage during radiological incidents to provide adequate and timely clinical interventions. However, there is currently a crucial shortage of methods capable of determining the extent of low-dose IR exposure to human beings. The phosphorylation of histone H2AX on serine 139 (designated γ-H2AX), a classic biological dosimeter, can be used to evaluate the DNA damage response. We have developed an estimation assay for low-level exposure to IR based on the mass spectrometry quantification of γ-H2AX in blood. Human peripheral blood lymphocytes sensitive to low-dose IR, maintaining low temperature (4°C) and adding enzyme inhibitor are proven to be key steps, possibly insuring that a stable and marked γ-H2AX signal in blood cells exposed to low-dose IR could be detected. For the first time, DNA damage at low dose exposures to IR as low as 0.01 Gy were observed using the sensitive variation of γ-H2AX with high throughput mass spectrometry quantification in human peripheral blood, which is more accurate than the previously reported methods by virtue of isotope-dilution mass spectrometry, and can observe the time effect of DNA damage. These in vitro cellular dynamic monitoring experiments show that DNA damage occurred rapidly and then was repaired slowly over the passage of post-irradiation time even after exposure to very low IR doses. This assay was also used to assess different radiation exposures at the in vitro cellular level. These results demonstrate the potential utility of this assay in radiation biodosimetry and environmental risk assessment.